Survey on Football League Table and Player Performance Prediction Using Data Science (International Journal of Innovative Research in Engineering & Management, 2021)
This article focuses on team performance as well as player  performance prediction, with team performance being evaluated  using a variety of machine learning algorithms and web scraping  methodologies. Data is refined and modified efficiently to get the  desired accurate results. Advanced Statistics is used to get results.  The prediction includes final league table of teams, whether a  team is going to have a better season than the previous one.  Prediction is also done to evaluate the rating of a defender.
Keywords: Sports analytics; Data mining; Web scrapping; Machine Learning